PENGARUH MANAJEMEN KELAS DAN KERMAHTAMAHAN TENAGA PENDIDIK TERHADAP MINAT ORANG TUA DALAM MENYEKOLAHKAN ANAK DI SEKOLAH DASAR SWASTA SANTA MARIA TARUTUNG - Meliana Kristina Sitanggang; Ibelala Gea; Lustani Samosir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The objectives of this study were: 1) To determine the influence of classroom management on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung; 2) To determine the influence of educators’ hospitality on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung; and 3) To determine the simultaneous influence of classroom management and educators’ hospitality on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung. The method used in this study was a quantitative research method. The population consisted of all parents of students from Grade I to Grade VI at Santa Maria Private Elementary School Tarutung, totaling 788 people, located in North Tapanuli Regency. The sample in this study was taken at 10% from each grade level, resulting in a total of 79 respondents. Data were collected using a closed-ended questionnaire consisting of 79 items. The results of data analysis showed that: 1) The calculated F-value was greater than the F-table value for the influence of classroom management on parents’ interest in enrolling their children, namely 70.555 > 3.07. Thus, it was found that there was a positive and significant influence of classroom management on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung, North Tapanuli Regency, amounting to 47.8%; 2) The calculated F-value was greater than the F-table value for the influence of educators’ hospitality on parents’ interest in enrolling their children, namely 72.745 > 3.07. Thus, it was found that there was a positive and significant influence of educators’ hospitality on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung, North Tapanuli Regency, amounting to 48.6%; and 3) The calculated F-value was greater than the F-table value for the simultaneous influence of classroom management and educators’ hospitality on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung, North Tapanuli Regency, namely 38.855 > 3.07. Thus, it was found that there was a positive and significant influence of classroom management and educators’ hospitality on parents’ interest in enrolling their children at Santa Maria Private Elementary School Tarutung, North Tapanuli Regency, amounting to 50.6%. Therefore, Ha was accepted and H0 was rejected.